Integrating Menstrual Health - Rehan Naqvi (MultiTech Publisher, 2023)
Menstruation is a natural and important part of the reproductive cycle, approximately half of the human population has or will experience it. Menstrual health (MH) is an integral part of sexual and reproductive health. Yet shame, stigma and misinformation around the menstrual life cycle undermine the well-being of women, girls, and people who menstruate, leaving them vulnerable to gender-based discrimination, child marriage, exclusion, violence, poverty, and untreated health problems. The Covid-19 pandemic has disrupted health delivery systems on a scale that has ushered in a new world. An estimated 1.8 billion women, girls, and gender non-binary people menstruate despite lockdown, restrictions on social mobility, stock outs, supply chain disruptions, lack of essential menstrual supplies, safe access to bathrooms, soap, water, and privacy. One in ten women in Africa skipped school when they menstruated, and too many girls struggled with chronic poverty. The year 2020 brought unprecedented disruption and change due to the COVID-19 pandemic, impacting various aspects of people's lives worldwide, including MH management. Despite these circumstances, an estimated 1.8 billion menstruating individuals faced difficulties in accessing essential menstrual supplies, safe facilities, and basic hygiene resources like soap and water. This lack of access has particularly affected girls' education and perpetuated chronic poverty.